BANK EFFICIENCY AND CONCENTRATION OF THE BANKING SECTOR IN THE CEE COUNTRIES (Polityki Europejskie, Finanse i Marketing)
The relationship between the structure of the banking market and efficiency of banks has been a subject of many studies for several decades. There is no uniform opinion on the correlation between these variables. The goal of the research is to investigate this relationship for 96 banks operating in eleven CEE countries in the years of 2005-2017. Bank efficiency scores are assessed with the SFA method and regressed with bank and macroeconomic characteristics. The results show that the efficiency of banks is positively affected by the concentration of the market on which they operate, as well as by the size of individual banks. This relationship is valid for all examined countries. Additionally, bank efficiency is positively impacted by improving the banking system. On the other hand, the GDP per capita, inflation rate and bank capital ratio are not conducive to bank efficiency.